Effects of Work Immersion on the Skills Acquisition of Senior High School Students in Public Secondary Schools - Jimenez, Arlene (International Journal of Sustainability and Advanced Integrated Research, 2026)
This study investigated the effects of work immersion on the skills acquisition of senior high school students in selected public secondary schools in Rizal, specifically Angono Senior High School, Cainta Senior High School, and Taytay Senior High School, during the School Year 2025–2026. Employing a descriptive survey research design, the study considered 50% of the total Grade 12 student population, totaling 926 respondents out of 1,852. Students were profiled according to age, sex, sibling position, number of children in the family, monthly family income, parents’ educational attainment, and parents’ occupation. Data were collected through a researcher-made questionnaire-checklist to assess students’ perceptions on the extent of work immersion effects on technical, interpersonal, and entrepreneurial skills. The study also examined the problems encountered in the implementation of the work immersion program.Findings revealed that most respondents are 16 years old and above, male, first or second born, from families with three or more children, with a majority earning a monthly family income below ₱15,000. Parents were generally college or high school undergraduates, with self-employment as the predominant occupation. Results indicated that work immersion significantly enhanced students’ technical, interpersonal, and entrepreneurial skills. No significant differences were observed in skills acquisition when analyzed by age, sex, sibling position, number of children, parents’ educational attainment, or occupation. However, a significant difference was noted in relation to monthly family income. Students reported encountering varied challenges in the program, with difficulty in performing tasks being the most prominent.The study concluded that work immersion has a significant positive impact on the skills acquisition of senior high school students, particularly influenced by family income. It is recommended that students be provided additional industry exposure to further enhance skill development. School authorities and personnel should prioritize addressing challenges in work immersion programs, and similar studies may explore additional variables to support effective skills development.